The Effect Of Convenience, Usefulness, Security And Confidentiality, Readiness Of Information Technology On The Use Of E-Filing For Individual Taxpayers (Case Study At Kpp Pratama West Tangerang) - Viola; Limajatini (Fakultas Bisnis, 2022)
The research here is carried out to test the influence of perceptions of convenience, perceptions of usefulness, security and confidentiality, readiness of information technology on the use of eFiling for individual taxpayers. In the research here, it uses data sources, namely primary data. Primary data that was obtained through the distribution of questionnaires. The sample of the research here is 53 Individual Taxpayers at the Tax Service Office (KPP) Pratama Tangerang Barat. The research data are here using SPSS version 25 software along with descriptive statics, reliability tests, validity tests, classical assumption tests, multiple linear regression analysis and hypothesis tests in processing. Based on the analysis that has been carried out, the results of the researcher can make conclusions that can be stated as follows: Perception of Ease does not affect the use of e-Filing, Perception of Usefulness does not affect the use of e-Filing, Security and Confidentiality affects the Use of e-Filing, Readiness of Information Technology does not affect the Use of e-Filing . Perception of Ease, Perception of Usefulness, Security and Confidentiality, Readiness of Information Technology jointly affect the Use of e-Filing.